2002
DOI: 10.1177/088307380201700908
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Macroscopic Correlates of Minicolumnar Pathology in Autism

Abstract: All subcortical arrangements are primarily nuclear in type. The cortex has been the first part of the brain to evolve a radial and laminar arrangement of cells. The resultant modular arrangement is based on the cell minicolumn: a self-contained ecosystem of connectivity linking afferent, efferent, and inerneuronal connections. Recently, the cell minicolumn has been found to be abnormal in patients with autism. This article relates different aspects of the cell minicolumn and larger-scale neuronal assemblies to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
130
2
7

Year Published

2004
2004
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 178 publications
(147 citation statements)
references
References 52 publications
(1 reference statement)
8
130
2
7
Order By: Relevance
“…Casanova et al [21,22] showed that in postmortem brain tissues from individuals with autism, the frontal and temporal cortical minicolumns were smaller, more numerous and less compact than those of non-autistic subjects. Alterations in the size and cellular distribution within cortical minicolumns in autism may reflect disturbances in the processing of thalamic inputs to cortex.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Casanova et al [21,22] showed that in postmortem brain tissues from individuals with autism, the frontal and temporal cortical minicolumns were smaller, more numerous and less compact than those of non-autistic subjects. Alterations in the size and cellular distribution within cortical minicolumns in autism may reflect disturbances in the processing of thalamic inputs to cortex.…”
Section: Discussionmentioning
confidence: 99%
“…-stereotypical behaviors, impaired verbal and nonverbal communication and blunted social interaction) are accompanied by structural and functional changes in cortex, cerebellum and amygdala [3,4,7,8,[19][20][21][22]37,38,49,55,67,101,125]. Structural and functional changes apparent in early childhood suggest that autism is a disorder of brain development [4,19,20,[37][38][39]111].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, we argue that MSDs are more closely related to the number of underlying neural units defining the morphology of the cortical surface. For example, many regions with significantly reduced MSDs (e.g., BA 3-4, 9, and 21-22) overlap with those that have previously been reported to have an increased minicolumn density in ASD, and decreased peripheral neurophil space (PNS) (48,49). Thus, our findings suggest that differences in MSDs may be closely related to the density of cortical minicolumns, and that minicolumns may be more unevenly distributed (and so more dense) in some regions relative to others.…”
Section: Discussionmentioning
confidence: 99%
“…Some of these include neocortical malformations such as irregular laminar patterns, thickened cortices, abnormally oriented pyramidal cells, and an increase in the number of layer one neurons [7]. In specific cortical areas, Casonanova et al [17] have reported the presence of smaller, more compact, and more numerous minicolumns. Regions in the forebrain that show reduced neuronal size and increased cell packing density include the hippocampus, subiculum, entorhinal cortex, mammilary bodies, anterior cingulated gyrus, septum and amygdala ( [38] and see [12,27,47] for recent reviews on autism neuropathology).…”
Section: Introductionmentioning
confidence: 99%